Pengaruh Kecerdasan Musikal terhadap Perkembangan Kognitif Anak Usia Dini di TK IT Nurul Ilmi - Nur Zakiyah; Dhiva Shahilla Saragih; Rizka Hasanah Nasution; Nur Hairani Siregar; Fauziah Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the influence of musical intelligence on the cognitive development of early childhood children at TK IT Nurul Ilmi. Employing a quantitative correlational approach, this research involves a sample of early childhood children at the kindergarten. The data collection instruments consist of a musical intelligence test and a cognitive development test. Data analysis using Pearson correlation indicates a positive and significant relationship between musical intelligence and cognitive development. The higher the musical intelligence, the higher the cognitive development. These findings suggest the integration of musical activities in the PAUD curriculum to stimulate children's cognitive development. Further research needs to be conducted to examine the most effective types of musical activities and other factors that influence this relationship.